Tyrphostin AG17 inhibits adipocyte differentiation in vivo and in vitro - Alberto Camacho (Lipids in Health and Disease, 2018)
Abstract Background Excessive subcutaneous adiposity in obesity is associated to positive white adipocyte tissue (WAT) differentiation (adipogenesis) and WAT expandability. Here, we hypothesized that supplementation with the insulin inhibitor and mitochondrial uncoupler, Tyrphostin (T-AG17), in vitro and in vivo inhibits adipogenesis and adipocyte hypertrophy. Methods We used a 3T3-L1 proadipocyte cell line to identify the potential effect of T-AG17 on adipocyte differentiation and fat accumulation in vitro. We evaluated the safety of T-AG17 and its effects on physiological and molecular metabolic parameters including hormonal profile, glucose levels, adipogenesis and adipocyte hypertrophy in a diet-induced obesity model using C57BL/6 mice. Results We found that T-AG17 is effective in preventing adipogenesis and lipid synthesis in the 3T3-L1 cell line, as evidenced by a significant decrease in oil red staining (p < 0.05). In obese C57BL/6 mice, oral administration of T-AG17 (0.175 mg/kg for 2 weeks) lead to decreased fat accumulation and WAT hypertrophy. Further, T-AG17 induced adipocyte apoptosis by activating caspase-3. In the hepatocytes of obese mice, T-AG17 promoted an increase in the size of lipid inclusions, which was accompanied by glycogen accumulation. T-AG17 did not alter serum biochemistry, including glucose, insulin, leptin, free fatty acids, creatinine, and aspartate aminotransferase. Conclusion T-AG17 promotes adipocyte apoptosis in vivo and is an effective modulator of adipocyte differentiation and WAT hypertrophy in vitro and in vivo. Therefore, T-AG17 may be useful as a pharmacological obesity treatment.